Trifurcated hepatic artery proper with unusual course and termination of right hepatic artery into fossa for gall bladder. - Naveen K,; Jyothsna P,; Swamy RS,; Anitha G,; Surekha DS,; Ashwini AP,; Satheesha NB, (Department of Surgery, UKM Medical Centre, 2014)
Variant vascular pattern affecting the hepatic artery is well documented. We here report a case of trifurcated hepatic artery proper associated with abnormal course, branching and termination of right hepatic artery. In the present case, hepatic artery proper trifurcated into right, middle and left branches about 2 cm before reaching porta hepatis. Left and middle braches entered the liver through the porta hepatis as normal but, the right hepatic artery took an unusual course towards the fossa for gall bladder and passed between portal vein behind and common hepatic duct, anteriorly. Just before its termination, it gave an additional hepatic branch to the liver and a cystic branch to the gall bladder. The rare course, branching pattern and abnormal termination of the right hepatic artery as reported here, are vulnerable to damage during intraoperative procedures if not carefully observed. Hence, prior knowledge of its variant anatomy is imperative during segmental resection of the liver and any intraoperative procedures performed in this region.